Tingkat Religiusitas Dengan Kebermaknaan Hidup Pada Survivor COVID-19 - Putri, Putri; Rifayanti, Rina; Kristanto, Andreas Agung (Psikoborneo: Jurnal Ilmiah Psikologi, 2022)
This study aims to determine the correlation between the level of religiosity and the meaning of life in COVID-19 survivors. This research method uses a quantitative approach. The subjects of this study were 150 early adults who had tested positive fir COVID-19 in Samarinda City, selected using a purposive sampling technique. The data collection method use is the meaningfulness of life scale and religiosity scale. The data analysis technique used is the Product Moment correlation statistical test. The results showed that there was a correlation between the level of religiosity and the meaningfulness of life in COVID-19 survivors with an r-count value of 0.697 and p = 0.000 < 0.05. which indicated that there was a correlation with a positive direction. That is, the higher the religiosity, the higher the meaning of life, conversely if the lower the religiosity, the lower the meaningfulness of life for COVID-19 survivors.  Penelitian ini bertujuan untuk mengetahui hubungan tingkat religiusitas dengan kebermaknaan hidup pada survivor COVID-19. Penelitian ini menggunakan metode kuantitatif. Responden yang terlibat dalam penelitian ini sebanyak 150 orang dengan usia dewasa awal yang pernah terkonfirmasi COVID-19 di Kota Samarinda dipilih melalui metode purposive sampling. Pengumpulan data menggunakan skala kebermaknaan hidup dan skala religiusitas. Teknik analisa menggunakan uji statistik korelasi product moment dengan hasil bahwa adanya hubungan tingkat religiusitas dengan kebermaknaan hidup pada survivor COVID-19 dengan nilai r hitung 0.697 dan p=0.000 < 0.05 yang menunjukkan adanya hubungan yang positif artinya semakin tinggi religiusitas maka semakin tinggi kebemaknaan hidup pada survivor COVID-19.